The cerebellum and parietal cortex play a specific role in coordination: a PET study. - Ramnani, N; Toni, I; Passingham, R; Haggard, P (2001)
The synthesis of complex, coordinated movements from simple actions is an important aspect of motor control. Lesion studies have revealed specific brain areas, particularly the cerebellum, to be essential for a variety of coordinated movements, and lend support to the view that the cerebellum is engaged in the integration of simple movements into compound ones. A PET study was therefore conducted to show which brain areas were active specifically during the coordinated execution of an arm and finger movement to visual targets. A two-by-two factorial design was employed, in which subjects either made arm or finger movements alone, made coordinated arm-finger movements, or made no movements. Voxels were identified where activity was significantly greater during the execution of coordinated movements than when movements were made alone and in which this increased activity could not be accounted for simply by the additive effects of the activations for each movement in isolation. The behavioral results showed that subjects coordinated arm and finger movements well during coordination scans. Coordination-specific activations were found in left anterior lobe and bilaterally in the paramedian lobules of the cerebellum. These are known to receive forelimb-specific spinocerebellar proprioceptive inputs that may be related to multijoint movements. The same areas also receive corticocerebellar afference from motor areas that may convey efference copy information to the cerebellum. Coordination-specific activations were also seen in areas of the posterior parietal cortex. The results provide direct evidence in healthy human subjects of specific cerebellar engagement during the coordination of movement, over and above the control of constituent movements.